RESPON DINAMIS TENSION LEG PLATFORM (TLP): STUDI KOMPARASI ANTARA PENGGUNAAN PONTON TELAPAK LINGKARAN DENGAN PONTON TELAPAK BUJUR SANGKAR - Jamiatul Akmal (Machine : Jurnal Teknik Mesin, 2022)
Tension Leg Platform (TLP) is an offshore platform that is usually used for oil and gas exploration activities in the deep sea. One of the problems is the extra shaking of the TLP in response to extreme ocean waves. Under certain conditions, especially in the deep seas of the ocean, these shocks can cause various disturbances, and even have the potential to damage structures. In this article, it is proposed to use a cylindrical pontoon to obtain a more stable dynamic response, which will then be compared with a pontoon with a square section which is commonly used so far. The dynamic response of both models was recorded by ultrasonic sensor and video tracker. The measurement results are displayed in a non-dimensional form, which is commonly known as the Response Amplitude Operator (RAO), which is the ratio between the displacement of the TLP to the wavelength. From this research, it was found that TLP with cylindrical pontoon section has a relatively stable response when compared to TLP with square pontoon section.